Interstitial lung disease following combined CDK4/6 inhibitor therapy and radiotherapy in advanced breast cancer: a case report - Guo, Lanlan; Dai, Yalan; Xiao, Mei; Li, Zhiping; Mao, Yinyan; Zhu, Zhiquan; Xu, Xiaolu; Peng, Peijian (Frontiers in Medicine, 2025)
BackgroundCyclin 4 and 6 dependent kinase inhibitors (CDK4/6i) have recently been approved for postmenopausal women diagnosed with hormone receptor–positive and HER2-negative metastatic breast cancer in combination with endocrine therapy. Research on the interaction of CDK4/6i and radiotherapy are scarce, but we observed some unexpected and severe toxicity, such as interstitial lung disease (ILD).CasesThrough blocking the transition from the G1 phase to the S phase (DNA synthesis phase), CDK4/6i inhibit tumor cell proliferation. The most common adverse event is neutropenia. Gastrointestinal toxicity, fatigue, QT Interval prolongation, increased liver enzymes, venous thromboembolic events, and ILD. Although ILD is very unlikely to occur, if suspected (e.g., worsening cough, dyspnea), interrupt treatment immediately and to evaluate the patient. In this study, we reported two cases of ILD in patients treated with the combination of radiotherapy and CDK4/6i. We also detailed the management strategy for patients who developed ILD, along with the subsequent clinical course and outcomes. Ultimately, with prompt and effective management, both patients showed improvement.ConclusionThese cases suggest that CDK4/6i may potentiate radiotherapy-associated pulmonary toxicity, and clinicians should exercise caution with this combination.